2015
DOI: 10.1063/1.4935054
|View full text |Cite
|
Sign up to set email alerts
|

The application of inelastic neutron scattering to explore the significance of a magnetic transition in an iron based Fischer-Tropsch catalyst that is active for the hydrogenation of CO

Abstract: An iron based Fischer-Tropsch synthesis catalyst is evaluated using CO hydrogenation at ambient pressure as a test reaction and is characterised by a combination of inelastic neutron scattering (INS), powder X-ray diffraction, temperature-programmed oxidation, Raman scattering, and transmission electron microscopy. The INS spectrum of the as-prepared bulk iron oxide pre-catalyst (hematite, α-Fe2O3) is distinguished by a relatively intense band at 810 cm(-1), which has previously been tentatively assigned as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 44 publications
(52 reference statements)
5
51
0
Order By: Relevance
“…This attribute is particularly accessible on direct geometry instruments such as MAPS and MERLIN [15,16]. A commonly adopted means of visualising this information is to use ''mitre'' plots [26], where the neutron scattering intensity is plotted as a function of energy (x, y axis) and momentum transfer (Q, x axis). Figure 2 shows the S(Q,x) mitre plots recorded on the MERLIN spectrometer for the clean (left hand frame) and reacted (right hand frame) samples with 4840 cm -1 incident energy.…”
Section: Inelastic Neutron Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…This attribute is particularly accessible on direct geometry instruments such as MAPS and MERLIN [15,16]. A commonly adopted means of visualising this information is to use ''mitre'' plots [26], where the neutron scattering intensity is plotted as a function of energy (x, y axis) and momentum transfer (Q, x axis). Figure 2 shows the S(Q,x) mitre plots recorded on the MERLIN spectrometer for the clean (left hand frame) and reacted (right hand frame) samples with 4840 cm -1 incident energy.…”
Section: Inelastic Neutron Scatteringmentioning
confidence: 99%
“…That work also outlines an increasing trend of using of INS to examine a variety of heterogeneously catalysed reaction systems [15]. For example, following on from the work of Silverwood et al who used INS to examine alumina-supported nickel catalysts applied to the dry [18-21] and steam [22] reforming of methane, Warringham and co-workers have used a combination of indirect [23] and direct [24][25][26] geometry INS spectrometers to investigate iron based FischerTropsch synthesis (FTS) catalysts. Moreover, Warringham et al [27] recently reported on sample environment details relevant to the acquisition of INS spectra of heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The iron oxide catalyst sample used for this investigation was prepared using the co-precipitation of iron nitrate (Sigma Aldrich, 99.99%) and sodium carbonate (Sigma-Aldrich, 99.99%). The preparative procedure utilises a batch reactor apparatus for reproducible sample synthesis and is described elsewhere [14]. The resulting slurry is filtered and washed with warm deionised water followed by a calcination step involving a step wise heating programme, with a maximum temperature of 623 K [14].…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…The preparative procedure utilises a batch reactor apparatus for reproducible sample synthesis and is described elsewhere [14]. The resulting slurry is filtered and washed with warm deionised water followed by a calcination step involving a step wise heating programme, with a maximum temperature of 623 K [14]. The procedure produces hematite (α-Fe 2 O 3 ) and an absence of promoters/modifiers.…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation